2022
DOI: 10.1128/spectrum.01929-21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plasmid and Resistance Gene Acquisition in the Emergence of ST23 Multi-Drug Resistant, Hypervirulent Klebsiella pneumoniae

Abstract: Hypervirulent Klebsiella pneumoniae (hvKp) has become the dominant pathotype in hospitals recently. The sequence type (ST) 23 hvKp, which are more commonly associated with the community-acquired infections previously, may have the capacity to acquire multidrug-resistant (MDR) phenotypes creating a new “superbug” (MDR-hvKp) in hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The other O loci, such as O1v2, that emerged in the study, should be sources of concern. The presence of iroB , iucA , peg344 , rmpA , and rmpA2 together is highly accurate for the identification hvKp, and we found that most of the ST65 genomes (83.0%, 78/94) harbored these five key virulence genes, suggesting that ST65 is a classic hvKp possessing a pLVPK-like plasmid, similar to ST23 ( 8 ). Among our 10 isolates, although the 5 above-described virulence genes were all positive, 3 isolates, P6, J4, and PEP3083, were negative for clb and ybt genes and received a virulence score of 3 with Kleborate software, whereas the other 7 isolates with clb and ybt genes had a score of 5.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The other O loci, such as O1v2, that emerged in the study, should be sources of concern. The presence of iroB , iucA , peg344 , rmpA , and rmpA2 together is highly accurate for the identification hvKp, and we found that most of the ST65 genomes (83.0%, 78/94) harbored these five key virulence genes, suggesting that ST65 is a classic hvKp possessing a pLVPK-like plasmid, similar to ST23 ( 8 ). Among our 10 isolates, although the 5 above-described virulence genes were all positive, 3 isolates, P6, J4, and PEP3083, were negative for clb and ybt genes and received a virulence score of 3 with Kleborate software, whereas the other 7 isolates with clb and ybt genes had a score of 5.…”
Section: Resultsmentioning
confidence: 64%
“…Most hvKp strains possess a thick capsule that serves as a barrier for the uptake of external genes ( 7 ). However, the typical hvKp strain, ST23, tends to acquire antimicrobial resistance genes via the plasmid and IS 26 , resulting in MDR-hvKp ( 8 ). Interestingly, bla CTX-M-like , not bla KPC or bla NDM , is common in MDR-ST23-hvKp ( 8 ), which is different from the ST11 endemic clone ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our isolate harbored an IncF plasmid, insertion sequences, and phage-associated proteins at regions containing ARGs and virulence genes, which reflect their possible role in the horizontal gene transfer and dissemination of such strains [16]. The IncF plasmids are thought to play a significant role in the acquisition of MDR genes [34,35], which could increase the chance for the acquisition of genes such as the bla KPC carbapenem resistance gene.…”
Section: Discussionmentioning
confidence: 83%
“…However, the adaptation and prevalence of hvKp in healthcare settings has become a recent threat [ 5 , 25 ], worsened by the high resistance of clinical strains [ 24 , 26 , 27 ]. While hvKp subtypes like CC23 commonly causing community-acquired infections have been more and more common in hospitals in recent years [ 28 ], a high proportion of CC258 isolates have been acquiring virulence plasmid becoming hvKp [ 3 , 4 ]; it was also observed that other common subtypes of cKp have obtained the virulence plasmid [ 5 ], becoming high antimicrobial-resistant hvKp themselves [ 26 ]. In this study, we found that among the four CC15 lineages, two clades in two different lineages obtained the pLVPK-like virulence plasmid independently, and one of them had the bla KPC-2 gene, becoming cr-hvKp.…”
Section: Discussionmentioning
confidence: 99%